The use of medicinal plants in the Aneuk Jamee tribe in Kota Bahagia, South Aceh District, Indonesia - NURSAMSU NURSAMSU; NURAINI NURAINI; TRI MUSTIKA SARJANI; MARDUDI MARDUDI (Society for Indonesian Biodiversity, 2024)
Abstract. Nursamsu, Nuraini, Sarjani TM, Mardudi. 2024. The use of medicinal plants in the Aneuk Jamee tribe in Kota Bahagia, South Aceh District, Indonesia. Biodiversitas 25: 2524-2540. The Aneuk Jamee tribe comes from the Acehnese language, namely